Exploring The Effect Of Reading Intensity In Mediating The Influence Of Classical Reading And Listening Strategies And Self-Intelligence On Al- Qur’an Reading Ability In Junior High School: PLS SEM Analysis - Sandra Anggarini, Wahyu; Wibowo, Arif; Daryono, Rihab Wit (DAYAH: Journal of Islamic Education, 2024)
This research aims to explore the role of reading intensity in mediating the influence of classical strategies and self-intelligence on the ability to read the Al-Qur'an. The method used in this research is purposive sampling with a random sampling method. The samples taken were 103 students at Madrasah Diniyah SMP PGRI Selur. Data collection in this research used a questionnaire in the form of a Likert scale with 4 alternative answers. Analysis in this research used PLS-SEM which aims to analyze data and test contextual models. From the results of the analysis, classical strategies do not have a significant effect on the reading intensity and ability to read the Al-Qur'an of students. From the results of this research, it was found that the dominant item determining the improvement in students' Al-Qur'an reading ability was self-awareness of 88.90%. So based on the results, reading intensity really mediates the influence of self-intelligence on the ability to read the Al-Qur'an and does not mediate classical strategies on the ability to read the Al-Qur'an. This research provides an illustration of how students' ability to read the Al-Qur'an can increase through their own intelligence and is also influenced by the level of intensity of reading it. Thus, this research can provide an in-depth picture of the influence of internal and external factors that can influence the level of success in improving the ability to read the Al-Qur'an in each student.